MRI appearance of multifocal Enterobacter cloacae abscesses in a preterm neonate - Hinman, Jason D.; Lerner, Jason; Salamon, Noriko (Journal of Pediatric Neuroradiology, 2012)
Bacterial brain abscesses are a potentially catastrophic complication of neonatal care requiring prompt diagnosis and management to avoid neurologic sequelae. Enterobacter species are known to cause multifocal lobar abscesses in the neonatal brain similar to other gram negative facultative anaerobic rods such as Citrobacter species. A preterm neonate developed Enterobacter cloacae cerebral abscesses after 3 weeks in the neonatal intensive care unit. Brain magnetic resonance imaging (MRI) demonstrated large periventricular ring-enhancing cystic-appearing lesions with hypointense internal stranding present on gradient echo sequences. The abscesses were treated with neurosurgical drainage and a prolonged course of antibiotics. We present the case details, radiologic findings including MRI features of Enterobacter cloacae abscesses and management of this difficult case.
Keywords: E. cloacae; brain abscess; neonate; MRI